Ideologies and National Identities - Lampe, John R.; Mazower, Mark (2006)
Twentieth-century Southeastern Europe endured three, separate decades of international and civil war, and was marred in forced migration and wrenching systematic changes. This book is the result of a year-long project by the Open Society Institute to examine and reappraise this tumultuous century. A cohort of young scholars with backgrounds in history, anthropology, political science, and comparative literature were brought together for this undertaking. The studies invite attention to fasci...